Performance, emissions, and combustion analysis of catalytic hydrothermal liquefaction derived fuel from Arthrospira platensis in IC engines: A predictive approach using least squares regression modeling - Mozas Santhose Kumar J; Prakash Ramakrishnan; Padmanathan Panneerselvam (Results in Engineering, 2025)
The increasing demand for sustainable fuels has driven interest in bio-oil as an alternative to fossil diesel. This study investigates the production of bio-crude oil from Arthrospira platensis biomass via catalytic hydrothermal liquefaction (HTL) and evaluates its potential use as a blend in internal combustion engines. The research focuses on the fuel properties, engine performance, emission characteristics, and combustion behavior of Arthrospira platensis oil (APO) and its blends with diesel. The engine was tested using pure diesel and three APO–diesel blends: APO10 (10 % v/v), APO20 (20 % v/v), and APO30 (30 % v/v). Among these, APO10 exhibited a 6 % reduction in brake thermal efficiency (BTE) and a slight increase in brake-specific fuel consumption (BSFC) compared to diesel. Emission analysis showed reductions in carbon monoxide (CO) and unburned hydrocarbons (HC) by approximately 20 % and 6.2 %, respectively. Combustion analysis revealed that the Peak in-cylinder pressures for APO blends were 70.3 bar for APO10, 70.1 bar for APO20, and 69.8 bar for APO30. Correspondingly, the peak HRR values were 35.2 J/degree for APO10, 34.4 J/degree for APO20, and 34.2 J/degree for APO30. A multiple linear regression model, developed using the least squares method, predicted blend ratio (R² = 0.96, RMSE = 2.20) and load (R² = 0.9995, RMSE = 1.11) based on performance and emission parameters. Hydrocarbons (p = 0.0028), CO (p = 0.0131), and exhaust gas temperature (EGT, p = 0.0145) were identified as statistically significant predictors. Additionally, a laboratory-scale cost assessment demonstrated the economic feasibility of catalytic HTL bio-oil production.